Shedding light on betL*: pPL2-lux mediated real-time analysis of betL* expression in Listeria monocytogenes. Issue 2 (2nd April 2016) - Keane, Shauna M.; Culligan, Eamonn P.; Hoffmann, Roland F.; Gahan, Cormac G.M.; Hill, Colin; Snelling, William J.; Sleator, Roy D.
ABSTRACT: We propose a mechanism of action for the betL * mutation which is based on DNA topology. Removing a single thymine residue from the betL σ A promoter's −10 and −35 spacer results in a 'twist'-mediated activation of transcription which accounts for the osmotolerance phenotype observed for strains expressing betL *.